Exploring the Relation: Does Forgiveness Enhance Interpersonal Problem Solving? - Çağla Girgin Büyükbayraktar; Süleyman Barbaros Yalçın; İsmail Yavuz Öztürk; Serkan Say (Behavioral Sciences)
This study explores the relationship between forgiveness and interpersonal problem-solving skills among university students using a correlational design. The sample includes 443 students aged 18–26 from Mersin and Selçuk Universities, selected through convenience sampling. Data were collected using the Heartland Forgiveness Scale, the Interpersonal Problem-Solving Inventory, and a personal information form. Pearson correlation and multiple regression analyses were conducted. Results indicate significant relationships between forgiveness and problem-solving skills. Forgiveness positively predicts constructive problem-solving (r = 0.45, p < 0.01) and negatively correlates with negative approaches to problems (r = −0.37, p < 0.01), lack of self-confidence (r = −0.29, p < 0.01), and unwillingness to take responsibility (r = −0.31, p < 0.01). Forgiveness explains 25.2% of the variance in negative approaches, 8% in constructive problem-solving, 13.4% in self-confidence, and 10.3% in responsibility avoidance. Self-forgiveness, forgiveness of others, and situational forgiveness are significant predictors across these dimensions. Findings suggest that forgiving students manage interpersonal conflicts more positively, with reduced negative emotions and avoidance behaviors. Promoting forgiveness and problem-solving skills through educational programs may enhance students’ social harmony, adjustment, and life satisfaction, benefiting both individuals and society. This aligns with existing literature highlighting the emotional and relational benefits of forgiveness.